Activity-regulated E3 ubiquitin ligase TRIM47 modulates excitatory synapse development - Sharma, Gourav; Banerjee, Sourav (Frontiers in Molecular Neuroscience, 2022)
Ubiquitin Proteasome System (UPS) has been shown to regulate neuronal development and synapse formation. Activity-dependent regulation of E3 ligase, a component of the UPS that targets specific protein for proteasome-mediated degradation, is emerging as a pivotal player for the establishment of functional synapses. Here, we identified TRIM47 as a developmentally regulated E3 ligase that is expressed in rat hippocampus during the temporal window of synapse formation. We have demonstrated that the expression of TRIM47 is regulated by glutamate-induced synaptic activity of hippocampal neurons in culture. The activity-dependent enhancement of TRIM47 expression is also recapitulated following object location test, a hippocampus-dependent spatial memory paradigm. We observed that this enhancement of TRIM47 expression requires NMDA receptor activation. The knockdown of TRIM47 leads to enhancement of spine density without affecting dendritic complexity. Furthermore, we observed an increase in excitatory synapse development upon loss of TRIM47 function. Comprehensively, our study identified an activity-regulated E3 ligase that drives excitatory synapse formation in hippocampal neurons.